Large yellow croaker peroxiredoxin IV protect cells against oxidative damage and apoptosis. (November 2020) - Wang, Xianhui; Li, Qiuhua; Mu, Pengfei; Guan, Yanyu; Chen, Xinhua; Ao, Jingqun
Highlights: A LYCK-PrxIV cell line stably expressing large yellow croaker peroxiredoxin IV was established. The level of intracellular NO, superoxide anion and H2 O2 in LYCK-PrxIV cells were significantly lower than those in control cells of LYCK-pcDNA3.1. When exposed to H2 O2, cell apoptosis was significantly alleviated in LYCK-PrxIV than in control cells. The ROS level and ATP content were maintained more stable in LYCK-PrxIV than in LYCK-pcDNA3.1 when treated by H2 O2 . The stably expressed Lc PrxIV attenuated the mRNA expression change of cytokine genes when cells were treated by H2 O2. Abstract: Oxidative stress and inflammation lead to cell damage and are implicated in many disease states. High concentrations of hydrogen peroxide (H2 O2 ) may mediate cells apoptosis by increasing intracellular reactive oxygen species (ROS) levels. In this study, we established a LYCK-PrxIV cell line (large yellow croaker head kidney cell line stably expressing peroxiredoxin IV). The level of nitric oxide (NO), superoxide anion and hydrogen peroxide (H2 O2 ) in this LYCK-PrxIV cells were significantly lower than those in control cells of LYCK-pcDNA3.1 (LYCK cell line stably transfected by pcDNA3.1 vector). Additionally, when exposed to H2 O2, cell apoptosis was significantly alleviated in LYCK-PrxIV than in control cells. Meanwhile, the ROS level and ATP content were maintained more stable in LYCK-PrxIV than in LYCK-pcDNA3.1. The over-expression of Lc PrxIV in LYCK-PrxIV cells induced a declined mRNA expression of Lc CXC, Lc CC, Lc IL-8 and Lc TNF-α2, as well as an increase of Lc IL-10 mRNA expression, when compared to LYCK-pcDNA3.1. On the other hand, the expression of chemokine Lc CXC, Lc CC and Lc TNF-a2 increased in LYCK-pcDNA3.1 after H2 O2 stimulation, while that of Lc IL-8 and Lc IL-10 decreased. The regualtion of gene expression in LYCK-PrxIV cells was almost the same as that in LYCK-pcDNA3.1, but the change fold was much more moderate. These results suggest that Lc PrxIV may be an indispensable ROS scavenger protecting LYCK cells against oxidative damage as well as the subsequent apoptosis and inflammatory response, which provides a clue that Lc PrxIV may be an assist in fish immune response.